TLR9-mediated dendritic cell activation uncovers mammalian ganglioside species with specific ceramide backbones that activate invariant natural killer T cells - Paget, Christophe; Deng, Shenglou; Soulard, Daphnée; Priestman, David A.; Speca, Silvia; Gerichten, Johanna von; Speak, Anneliese O.; Saroha, Ashish; Pewzner-Jung, Yael; Futerman, Anthony H.; Mallevaey, Thierry; Faveeuw, Christelle; et al. (PLoS biology, 2019)
CD1d-restricted invariant natural killer T (iNKT) cells represent a heterogeneous population of lipid-reactive T cells that are involved in many immune responses, mediated through T-cell receptor (TCR)-dependent and/or independent activation. Although numerous microbial lipid antigens (Ags) have been identified, several lines of evidence have suggested the existence of relevant Ags of endogenous origin. However, the identification of their precise nature as well as the molecular mechanisms involved in their generation are still highly controversial and ill defined. Here, we identified two mammalian gangliosides—namely monosialoganglioside GM3 and disialoganglioside GD3—as endogenous activators for mouse iNKT cells. These glycosphingolipids are found in Toll-like receptor-stimulated dendritic cells (DC) as several species varying in their N-acyl fatty chain composition. Interestingly, their ability to activate iNKT cells is highly dependent on the ceramide backbone structure. Thus, both synthetic GM3 and GD3 comprising a d18:1-C24:1 ceramide backbone were able to activate iNKT cells in a CD1d-dependent manner. GM3 and GD3 are not directly recognized by the iNKT TCR and required the Ag presenting cell intracellular machinery to reveal their antigenicity. We propose a new concept in which iNKT cells can rapidly respond to pre-existing self-molecules after stress-induced structural changes in CD1d-expressing cells. Moreover, these gangliosides conferred partial protection in the context of bacterial infection. Thus, this report identified new biologically relevant lipid self-Ags for iNKT cells.
Gesehen am 11.07.2019